1973
DOI: 10.1079/bjn19730117
|View full text |Cite
|
Sign up to set email alerts
|

Progressive changes in serum cortisol, insulin and growth hormone concentrations and their relationship to the distorted amino acid pattern during the development of kwashiorkor

Abstract: I . During the initial stages of the development of hypoalbuminaemia, with concentrations between 25 and 30 g,J, fasting serum cortisol and growth hormone values remained normal. Corresponding fasting serum insulin concentrations were, however, significantly above normal. During the same period, called phase H, valine concentrations were moderately low hut alanine Concentrations mere raised.2. In more severe hypoalbuminaemia, culminating in kwashiorkor, a marked switch in hormonal balance occurred. Tnsulin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
4

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 8 publications
4
40
0
4
Order By: Relevance
“…This discrepancy needs further study . LUNN et al (8) observed that the plasma alanine concentration in infants with kwashiorkor was increased by high-carbohydrate food . Moreover, ADIBI (17) observed a high concentration of plasma alanine in adults fed a protein-free diet , but a low concentration in starved subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy needs further study . LUNN et al (8) observed that the plasma alanine concentration in infants with kwashiorkor was increased by high-carbohydrate food . Moreover, ADIBI (17) observed a high concentration of plasma alanine in adults fed a protein-free diet , but a low concentration in starved subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in concentration of plasma EAA was primarily due to reduced supply of these amino acids but it was also related to energy supply, because addition of extra energy to the low-egg-protein diet resulted in reduction of plasma EAAs. Further evidence that decrease in the levels of plasma EAAs in protein deficiencies may be intensified by supply of excess energy is as MA FREE AMINO ACIDS IN MEN 305 follows: (i) LUNN et al (8) observed hyperinsulinemia resulting from ingestion of high-carbohydrate meals during the early stage of kwashiorkor and suggested that utilization of amino acids in tissues was enhanced in this condition; (ii) We found previously (9) that the nitrogen balance and NPU observed with submaintenance N intakes were greatly affected by the protein sparing effect of energy intake; (iii) MUNRO et al (20) showed that the lowered levels of plasma amino acids observed in subjects loaded with glucose were due to enhanced utilization of the amino acids in the muscle through the action of insulin; and (iv) recently, GRIMBLE and WHITEHEAD (7) also reported similar findings to (iii), in patients with kwashiorkor after administration of glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 No significant correlation was found between serum albumin and Cortisol levels in the malnourished children before treatment. This finding, in concert with observations that the serum Cortisol concentration was elevated in marasmic children despite their normal circulating albumin levels, casts doubt on the proposed relationship between the decrement in albumin and the elevation of Cortisol levels in the basal state in PEM.…”
Section: Discussionmentioning
confidence: 94%
“…Some report lower responses in children with kwashiorkor than in those with marasmus, 12 although others have reported the opposite. 13 Hypoglycemia, hypoalbuminemia, infections, and the stress of dietary restriction are proposed by different authors to correlate with the Cortisol levels in PEM, 10,[14][15][16][17] but further information of the role played by these factors is needed.…”
Section: -4mentioning
confidence: 99%